Separation of Acetic Acid from Aqueous Solution using Various Organic Solvents - Khan, Md. Zaved Hossain (Journal of Science and Technology, 2014)
In the study a model has been developed to separate the acetic acid from aqueous solution by liquid-liquid extraction and find out the proper solvent for this separation. Various solvents such as n-butanol, iso butanol, amyl alcohol and ethyl acetate are used for separation of acetic acid from water. The binodal curves (mutual solubility curves) for acetic acid distributed between water and an organic solvent were obtained by titrating known mixtures of two components (water and solvents) with the third component acetic acid to the point of first appearance of permanent turbidity. In order to determine the tie-lines, the absorbance of the coexisting phases, obtained by the separation of ternary mixtures within the binodal curve are needed to be determined. The absorbance of each point had been determined by a UV spectrophotometer. Distribution diagrams are obtained by plotting weight percent of acetic acid in solvent phase against the weight percent of acetic acid in water phase. Selectivity diagrams are also obtained by plotting (wt. % of acetic acid) / (percent of acetic acid + percent of water) in solvent phase against the same quantity in the diluent phase. The separation factor is determined numerically from the tie-line data.